2020
DOI: 10.1002/elps.202000107
|View full text |Cite
|
Sign up to set email alerts
|

Four‐step approach to efficiently develop capillary gel electrophoresis methods for viral vaccine protein analysis

Abstract: Vaccines against infectious diseases are urgently needed. Therefore, modern analytical method development should be as efficient as possible to speed up vaccine development. The objectives of the study were to identify critical method parameters (CMPs) and to establish a set of steps to efficiently develop and validate a CE‐SDS method for vaccine protein analysis based on a commercially available gel buffer. The CMPs were obtained from reviewing the literature and testing the effects of gel buffer dilution. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…16 SDS-CGE has been widely used in the biopharmaceutical industry to analyze therapeutic proteins in a simple and robust manner for drug development and commercialization; however, limited studies have been published to date on the fundamental aspects of this transitionally cross-linked chemical gel separation matrix. 17 Understanding of the migration and separation behavior of SDS−protein complexes will aid in the optimization of the analysis of specific biopharmaceuticals. This article reports on the effect of the concentration and ratio of the dextran monomer (2 MDa) and borate cross-linker on molecular sieving and separation performance in capillary SDS gel electrophoresis of proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 SDS-CGE has been widely used in the biopharmaceutical industry to analyze therapeutic proteins in a simple and robust manner for drug development and commercialization; however, limited studies have been published to date on the fundamental aspects of this transitionally cross-linked chemical gel separation matrix. 17 Understanding of the migration and separation behavior of SDS−protein complexes will aid in the optimization of the analysis of specific biopharmaceuticals. This article reports on the effect of the concentration and ratio of the dextran monomer (2 MDa) and borate cross-linker on molecular sieving and separation performance in capillary SDS gel electrophoresis of proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides monitoring the purity and integrity of the viral particles, the method was also used to study its interaction and stoichiometry with the corresponding mAb. Other CE modes such as CGE, and SDS‐CGE were reported for identification, quantification, and purity analysis of vaccine products [130–133].…”
Section: Analysis Of New Modality Protein Therapeuticsmentioning
confidence: 99%
“…Multiple reports have been published for vaccine products characterization [130–133]. For example, one study reported CZE‐UV for quantification of a subunit vaccine [130].…”
Section: Analysis Of New Modality Protein Therapeuticsmentioning
confidence: 99%
“…The separation conditions were 20°C capillary temperature, and 80% v:v gel buffer. See Geurink et al for more details [34].…”
Section: Ce-sds For Sabin Inactivated Polio Proteinmentioning
confidence: 99%